Pesticides Advances in Chemical and Botanical Pesticides - Soundararajan, R.P (IntechOpen, 2012)
Pesticides are considered as potential molecules to combat insects, pests, diseases and weeds in agricultural, horticultural cropping system as well as health management systems. Pesticides of chemical origin are highly effective against the target organism. However, the chemical pesticides have toxic effects on several non-target species and the growing environmental concerns raises the issues of safety and evaluation of toxicity. In this book the effects of chemical pesticides on fishes, earthworms, beneficial microbes and natural enemies in agricultural ecosystems are discussed. Furthermore, pesticides have the properties to disrupt endocrine and non-traditional pesticide compounds have been elaborately narrated. The recent technology on use of biomarkers in pesticide assay is described in two chapters. Some of plants having pesticidally active compounds are described. Use of biotechnological approaches for insect pest management and a new approach to recognize larva in the field by LIRA classifier system are two more interesting chapters of the book.